Near Net Shape Manufacturing Processes - Gupta, Kapil (Materials Forming, Machining and Tribology, 2019)
This book covers the mechanism, salient features, and important aspects of various subtractive, additive, forming and hybrid techniques to manufacture near net-shaped products. The latest research in this area as well as possible future research are also highlighted. .